2015
DOI: 10.2147/dnnd.s37268
|View full text |Cite|
|
Sign up to set email alerts
|

Critical appraisal of rotigotine transdermal system in management of Parkinson’s disease and restless legs syndrome – patient considerations

Abstract: Rotigotine (RTG) is a dopamine agonist that is used as mono and adjunct therapy to treat Parkinson's disease, and as therapy for moderate-to-severe restless legs syndrome. RTG is the only dopamine agonist currently available as a 24-hour/day transdermal system, providing once-a-day dosing. As a transdermal patch, RTG bypasses the gastrointestinal tract, making it a treatment option for patients with dysphagia. The use of RTG also avoids the need to schedule administration of medication around meals. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…In a randomized controlled study of over 300 patients, the efficacy of levodopa and cabergoline in the treatment of RLS was compared; the study showed a greater efficacy on symptoms for the cabergoline treatment, while patients in the levodopa treatment group reported better tolerability [ 103 ]. Pramipexole, rotigotine, and ropinirole have also shown good efficacy in controlling RLS symptoms [ 104 , 105 , 106 ]. Finally, both immediate-release and extended-release ropinirole have been shown to have a significant effect in mitigating daytime sleepiness episodes in EDS [ 107 ].…”
Section: Available Drugs and State Of Art Of Treatmentmentioning
confidence: 99%
“…In a randomized controlled study of over 300 patients, the efficacy of levodopa and cabergoline in the treatment of RLS was compared; the study showed a greater efficacy on symptoms for the cabergoline treatment, while patients in the levodopa treatment group reported better tolerability [ 103 ]. Pramipexole, rotigotine, and ropinirole have also shown good efficacy in controlling RLS symptoms [ 104 , 105 , 106 ]. Finally, both immediate-release and extended-release ropinirole have been shown to have a significant effect in mitigating daytime sleepiness episodes in EDS [ 107 ].…”
Section: Available Drugs and State Of Art Of Treatmentmentioning
confidence: 99%